Study on the Distribution Characteristics of Tribolium Castaneum in Wheat Grain Heap - ZHANG Ze-yu; ZHOU Guo-xin; CUI Miao; WANG Zhong-ming (Liang you shipin ke-ji)
Using a new type of insect probe trap, the activity and distribution of Tribolium castaneum in wheat grain bulks inside experimental silos were collected and analyzed to investigate its distribution patterns and main influencing factors within the grain bulks. An equation for estimating insect population density was established to provide a scientific basis for accurate monitoring and early warning. The results showed that the daily capture of Tribolium castaneum did not change significantly over time. When the insect population density was low, Tribolium castaneum was mainly distributed in the top and middle layers of the grain bulk. When the insect population density was high, Tribolium castaneum was uniformly distributed within the grain bulk. Tribolium castaneum exhibited thermophilic and hygrophilic behaviors, with an optimal activity temperature range of 22~30 ℃ and a relative humidity range of 40%~53%. By comprehensively analyzing the spatial and temporal distribution patterns of the insect population and the effects of temperature and humidity, the actual insect population density could be estimated based on the number of insects captured by the probe traps. The equation for estimating the insect population density was: y = 10.566 – 0.321 × x1 – 0.017 × x2 + 0.026 × x3, x1: temperature (℃), x2: relative humidity (%), x3: number of insects captured.